Randomized comparison between objective-based lectures and outcome-based concept mapping for teaching neurological care to nursing students. (February 2016) - Hsu, Li-Ling; Pan, Hui-Ching; Hsieh, Suh-Ing
Summary: Background: Pre-registration programs have been found to insufficiently prepare nurses for working in the neurosciences specialism. Effective approaches to neurology education are important, not only to enhance motivation to learn, but also for learners to develop basic competence in handling patients with neurological problems. Objectives: To demonstrate that outcome-based course design using concept mapping would bring about significant differences in the nursing students' competency, cognitive load, and learning satisfaction with the neurological care course. Methods: A two-group pretest and post-test experimental study was administered. Two of the four clusters of participants were randomly assigned to the experimental group for experiencing an outcome-based course design using concept mapping, and the rest were designated the control group to be given objective-based lectures only. The Competency Inventory of Nursing Students, Cognitive Load Scale of Neurological Nursing, and Learning Satisfaction Scale of Neurological Nursing were used in this study for the students to rate their own performance. In addition, The Concept Map Scoring Scale was used in the experimental group for examining students' concept mapping ability. Results: Significant increases of mean nursing competency scores in both groups from pre-test to post-test were found. There was no statistically significant difference in mean nursing competency score between the experimental group and the control groups at post-test. The mean cognitive load score of the experimental group was lower than the control group at post-test. The mean learning satisfaction scores of the experimental group were higher than the control group. Conclusions: This article provides that outcome-based concept mapping as educational method could encourage a group of nursing students to take a bio-psycho-social approach to medicine, which might ultimately result in better nursing care quality. Highlights: Implementing two educational methods in teaching neurological care to nursing students. An outcome-based approach utilizing concept mapping principles was more effective than an offered didactic, objective-based approach. This approach can be seen as raising the value of the topic in this study, perhaps even contributing to the development of an outcome-based teaching module. The findings of this study may provide constructive guidance for related studies in the future.